SUATU TINJAUAN TERHADAP SISTEM PELAYANAN BAGI MASYARAKAT MISKIN SERTA CARA PENANGGULANGANYA BERDASARKAN UNDANG-UNDANG NO.23 TAHUN 1992 - Irfan Afdoli Harahap; Taufik Siregar; Abi Jumroh Harahap (Jurnal Ilmiah Penegakan Hukum, 2016)
The discussion of this thesis is about a review of the service system for the poor as well as how to overcome them based on law no.23 of 1992. The health care system for the poor in the sei rengas village is very efficient, because the sei rengas village collaborates with the puskesmas in the kelurahan that. And sei rengas residents who are able to help provide donors to underprivileged people in health.